2022
DOI: 10.7759/cureus.23776
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal Shunt and Gastrostomy Tube Placement and Timing: A Database Analysis

Abstract: Background Debate exists about the safety of ventriculoperitoneal shunt placement in the presence of a gastrostomy tube and the timing of these procedures from each other. Using a large database, we sought to determine the rates of shunt infection and revision in patients who had both devices placed, based on the timing between procedures. Methods We performed a retrospective database analysis using a multi-institutional database (TriNetX), looking at all patients diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…A 2022 retrospective study by Hallan and Rizk analyzed the rate of infection among 4,269 patients with a VPS and G-tubes in a retrospective database. The study reported no significant difference in infection or revision rates between the same-day G-tube and VPS placement when compared to placement within one to ten days, eleven to thirty days, or greater than one month [24].…”
Section: Ventriculoperitoneal Shuntmentioning
confidence: 86%
See 2 more Smart Citations
“…A 2022 retrospective study by Hallan and Rizk analyzed the rate of infection among 4,269 patients with a VPS and G-tubes in a retrospective database. The study reported no significant difference in infection or revision rates between the same-day G-tube and VPS placement when compared to placement within one to ten days, eleven to thirty days, or greater than one month [24].…”
Section: Ventriculoperitoneal Shuntmentioning
confidence: 86%
“…It is common for VPS patients to require G-tubes for nutritional support, but complications may arise when the VPS catheter has already been implanted into the peritoneal cavity or from simultaneous placement. [24,25]. Placing a G-tube following a VPS increases the risk of infection and shunt malfunction [25].…”
Section: Ventriculoperitoneal Shuntmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on an ideal interval and sequence of gastrostomy and VPS placement to mitigate the risks of infection and revision are mixed and inconclusive for the adult population. [9][10][11][12][13]15,16,21 Perhaps the most notable study was conducted recently in 2022 by Hallan and Rizk. 16 Using a multi-institutional database (TriNetX), they evaluated 4269 patients categorized into cohorts of patients with varying procedure intervals.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13]15,16,21 Perhaps the most notable study was conducted recently in 2022 by Hallan and Rizk. 16 Using a multi-institutional database (TriNetX), they evaluated 4269 patients categorized into cohorts of patients with varying procedure intervals. They found no significant difference in shunt infection or revision rates between intervals, including same day vs gastrostomy after VPS placement.…”
Section: Discussionmentioning
confidence: 99%